Salud mental y su incidencia en el rendimiento deportivo de un adolescente de 14 años en la Federación Deportiva de Los Ríos - Salvatierra Morales, David Emanuel (2022)
This case study deals with the analysis of the incidence of the mental health of a 14 year old adolescent in the sports federation of the rivers (FEDERIOS) located in the city of Babahoyo. In the sports performance of the same due to problems after suffering an accident in a race, in order to also establish a proposal for therapeutic intervention, to help him overcome the state in which he is currently and optimize his level of competition in the future. As evaluation instruments, the Beck depression inventory was used on the patient, which yielded a result of 15, which means that the patient has a mild depression. The Hamilton anxiety scale was also applied, which resulted in the presence of a psychic anxiety of 11 and somatic anxiety of 14, which shows a moderate level of anxiety, after the evaluation of the results obtained, it can be evidenced that the patient presents a picture of post-traumatic stress due to the event experienced in the race, which prevents him from approaching or performing activities that are related or similar to this event, generating evident somatic symptoms such as paralysis, sweating and nervousness. From the cognitive behavioral approach which was chosen to work this case, the application of techniques such as: Differentiating between event, thought and feeling, Examining evidence, Explaining how thoughts create feelings and Classifying the Degree of Emotion and the Degree of Belief in a Thought, scored from 0 to 100%, the same that were helpful for the patient to modify the thoughts responsible for negative emotions and anxious response, ending in the training in a passive relaxation technique to manage stress in pressure situations.